The role of long-chain polyunsaturated fatty acids in the treatment of cancer Cachexia and tumour growth in patients with malignant diseases: A review - Elizabeth A Symington; Gerda J Gericke (AOSIS, 2008)
Recent studies show that ω-3 polyunsaturated fatty acids (PUFAs) have the capacity to modulate cancer outcomes. The body responds to cancer in the same way that it responds to inflammation and wound healing. Nutrients with anti-inflammatory effects could therefore be expected to play a role in cancer treatment. This review focuses on the role of ω-3 PUFAs in tumourigenesis and cancer cachexia. Studies indicate that eicosapentaenoic acid (EPA) supplementation may promote arrest of tumour growth and reduce cell proliferation. Patients need to consume at least 2 g of EPA per day for it to have a therapeutic effect. Positive outcomes related to cachexia include diminished weight loss, increased appetite, improved quality of life and prolonged survival, although there is controversy regarding these clinical outcomes. The effects of ω-3 PUFAs on tumourigenesis and cachexia are viewed in the context of altered lipid and protein metabolism. This altered metabolism usually experienced by cancer patients results in increased formation of proinflammatory eicosanoids and cytokines. Cytokines play an indirect role by stimulating the production of arachidonic acid-derived eicosanoids, which support inflammation, cell proliferation and angiogenesis, and inhibit apoptosis. It can be concluded that ω-3 PUFA supplementation offers a means of augmenting cancer therapy, inhibiting tumourigenesis and possibly contributing to cachexia alleviation. Opsomming Onlangse studies toon dat ω-3-poli-onversadigde vetsure (POVSe) oor die vermoë beskik om kankeruitkomste te moduleer. Die liggaam reageer op kanker op dieselfde wyse as wat dit op inflammasie en wondgenesing reageer. Daar kan dus verwag word dat voedingstowwe met 'n anti-inflammatoriese uitwerking 'n rol in die behandeling van kanker kan speel. In hierdie oorsig word daar op die rol van ω-3-POVSe in tumorigenese en kankerkageksie gefokus. Studies dui daarop dat eikosapentanoënsuur- (EPS-)aanvulling tumorgroei moontlik kan stuit en selproliferasie verlaag. Pasiënte moet minstens 2 g EPS per dag inneem om 'n terapeutiese uitwerking te verseker. Positiewe uitkomste verbonde aan kageksie sluit minder gewigsverlies, beter eetlus, beter lewensgehalte en langer oorlewing in, hoewel daar 'n geskil bestaan oor hierdie kliniese uitkomste. Die uitwerking van ω-3-POVSe op tumorigenese en kageksie word in die konteks van gewysigde lipied- en proteïenmetabolisme beskou. Die metabolisme wat dikwels in kankerpasiënte voorkom, lei tot 'n verhoogde vorming van pro-inflammatoriese eikosanoïede en sitokiene. Sitokiene speel ook 'n indirekte rol deur die produksie van aragidoonsuur-afkomstige eikosanoïede te stimuleer. Laasgenoemde ondersteun inflammasie, selproliferasie en angiogenese, en inhibeer apoptose. Die gevolgtrekking kan gemaak word dat ω-3-POVS-aanvulling 'n manier is om kankerterapie uit te brei, tumorigenese te inhibeer en moontlik tot die verligting van kageksie by te dra.